From Landlords to Software Engineers: Migration and Urbanization among Tamil Brahmans - C . J . FULLER AND HARIPRIYA NARASIMHAN (Comparative Studies in Society and History, 2008)
In south India’s rapidly expanding information technology (IT) industry, the small, traditional elite of Tamil Brahmans is disproportionately well rep- resented. Actually, no figures to confirm this assertion exist, but all the circum- stantial evidence suggests that it is true, especially among the IT professionals and software engineers employed by the leading software and services compa- nies in Chennai (Madras). 1 Since the nineteenth century, Tamil Brahmans have successfully entered several new fields of modern professional employment, particularly administration, law, and teaching, but also engineering, banking, and accountancy. Hence the movement into IT, despite some novel features, has clear precedents. All these professional fields require academic qualifica- tions, mostly at a higher level, and the Brahmans’ success is seemingly explained by their standards of modern education, which reflect their caste tra- ditions of learning.